2002
DOI: 10.2981/wlb.2002.022
|View full text |Cite
|
Sign up to set email alerts
|

Molecular population phylogeny of the hazel grouse Bonasa bonasia in East Asia inferred from mitochondrial control‐region sequences

Abstract: A total of 62 mitochondrial haplotypes were detected from 174 samples of hazel grouse Bonasa bonasia from Hokkaido, Primorskii, Sakhalin, Magadan, Siberia and Bohemia using 428 bp of the mitochondrial DNA control region. Haplotype diversity for four populations in Hokkaido was more than 0.8, suggesting that a reasonable population size had been maintained throughout their history. Haplotypes from Hokkaido and haplotypes from Primorskii were clearly separated from other Eurasian continent haplotypes, not only i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 18 publications
0
21
0
Order By: Relevance
“…In Sweden as well as throughout most of its range, the hazel grouse distribution is tied to the occurrence of continuous old-growth coniferous forest. Previous genetic studies have used a phylogeographic approach to detect broad patterns of genetic structure within the entire range of the species (Baba et al, 2002). There are, however, hitherto no studies of genetic structure at the regional level, that is at intermediate geographic scales.…”
Section: Introductionmentioning
confidence: 99%
“…In Sweden as well as throughout most of its range, the hazel grouse distribution is tied to the occurrence of continuous old-growth coniferous forest. Previous genetic studies have used a phylogeographic approach to detect broad patterns of genetic structure within the entire range of the species (Baba et al, 2002). There are, however, hitherto no studies of genetic structure at the regional level, that is at intermediate geographic scales.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, all genetic studies on hazel hens performed until now have focused on the phylogeography of the species [12,13] and population genetics in continuous habitat [14]. Phylogenetic studies based on mitochondrial DNA have identified high genetic variability in a population from Hokkaido (Japan) and a clear separation between this population and birds from continental Asia [12,13]. A population study based on nuclear microsatellite markers has also shown high within-population genetic variability and rather high gene flow among subpopulations in Sweden [14], despite the low dispersal ability of this species.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, all genetic studies on hazel hens performed until now have focused on the phylogeography of the species [12,13] and population genetics in continuous habitat [14]. Phylogenetic studies based on mitochondrial DNA have identified high genetic variability in a population from Hokkaido (Japan) and a clear separation between this population and birds from continental Asia [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, eastern European and Asian refugia that have been suggested are: (1) the Carpathians (Jaarola and Searle 2002;Deffontaine et al 2005); (2) the Caspian region and Middle East (Durand et al 1999, LiukkonenAnttila et al 2002Hansson et al 2008); (3) Beringia and eastern Siberia (Holder et al 1999;Abbott et al 2000;Holder et al 2000;Skrede et al 2006); (4) Moscow (Lagercrantz and Ryman 1990); (5) Manchuria and Mongolia (Baba et al 2002); and (6) the southern Ural Mountains, where most of Taiga species might have started a postglacial expansion (Goropashnaya et al 2004;Schmitt 2007).…”
Section: Postglacial Colonisationmentioning
confidence: 99%
“…The mutation rate of the avian control region is uncertain (Hansson et al 2008), but we used a mutation rate between 9.12 9 10 -5 and 3.65 9 10 -4 (3 years generation time and 304 bp) for the domain I (Randi et al 1999), which is a hypervariable region in the CR (Quinn 1992;Holder et al 1999;Randi et al 1999;Baba et al 2002;Ruokonen and Kvist 2002).…”
Section: Statistical Analysesmentioning
confidence: 99%